Pengaruh Komunikasi Persuasif Pendamping PKH Terhadap Perubahan Perilaku Ekonomi Pada Implementasi Family Development Session Di Kota Bandar Lampung - Umi Rojiati; Rini Setiawati (STAI Bumi Silampari, 2025)
This study aims to determine the influence of persuasive communication of PKH companions in Bandar Lampung City in the implementation of Family Development Session (FDS) and find out whether there is a change in economic behavior. The method used in this study is explanatory quantitative. The population of 38,286 people is taken from the final closing data of the 2022 final stage. The sampling method used is the regional sampling technique (Area Sampling). The data analysis used is Structural Equation Modeling Partial Least Square (SEM-PLS) with SmartPLS 4 software. The results of the Outer Model Bootsraping show that each indicator on all constructs has proven to be valid and reliable in reflecting each construct. Then the results of the Inner bootstrapping model found that the influence of persuasive communication of PKH Companions in Bandar Lampung City on changes in economic behavior and its influence proved significant for each variable. PKH's companion persuasive communication found a T-Statitik value of 128,629 which is greater than 1.96 with a standard deviation finding a number of 0.008 that does not exceed 2 so that it is stated that the variable has a significant influence. The amount of influence on economic behavior found results, namely increased after KPM followed FDS. The r- square value from before FDS was 0.088 or 9% while after FDS found the result of 0.967 R-square value of 97%. From the acquisition of these data, the percentage of total influence produced is 88%